Recurrent respiratory obstruction from a mediastinal bronchogenic cyst. Issue 8 (August 1992) - Johnston, S R; Adam, A; Allison, D J; Smith, P; Ind, P W
Abstract : A large mediastinal bronchogenic cyst presented acutely with paroxysmal atrial fibrillation and severe airflow obstruction. The patient had experienced identical symptoms on two other occasions over the previous 24 years. These had been previously misdiagnosed as due to a mediastinal lymphoma. Percutaneous extrapleural aspiration successfully decompressed the cyst with substantial improvement in lung function. Recurrent swelling of the cyst occurred that could not be relieved surgically. After repeat aspiration percutaneous instillation of bleomycin and alcohol has been used to prevent further increase in the size of the cyst.